Tax-Benefit Systems and the Gender Gap in Income - Karina Doorley; Claire Keane (Institute of Labor Economics (IZA), 2020)
The gender wage gap and the gender work gap are sizable, persistent and well documented for many countries. The result of the gender wage and gender work gap combined is an income gap between men and women. A small literature has begun to examine how the tax-benefit system contributes to closing gender income gaps by redistributing between men and women. In this paper, we study the effect of tax-benefit policy on gender differences in income. We use microsimulation models linked to survey data to estimate gender gaps in market income (before taxes and transfers) and disposable income (after taxes and transfers) for each country. We develop a method to isolate the relative contributions of the gender wage gap and the gender work gap to the overall gap in income between men and women. We then decompose the difference between the gender gap in market income and the gender gap in disposable income into (i) the relative contribution of taxes and benefits in each country and (ii) the relative cushioning of the gender wage gap and gender work gap. Policy conclusions are drawn about redistribution between men and women.
Keywords: J16; J31; 330; gender inequality; decomposition; tax-benefit system